Multi-layer color fluorescent engraving method for Betashes

By setting an optical isolation layer between multiple fluorescent coatings and using a transparent protective film, the problem of optical interference between fluorescent layers is solved, improving visual clarity and color contrast, and enhancing the artistry and aesthetics of palm leaf carving.

CN121004111APending Publication Date: 2025-11-25北京纳福玉器中心(个人独资)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511194781.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

During the laser engraving process of multi-layer fluorescent coatings, optical interference between different fluorescent layers leads to blurred visual effects and reduced color contrast, affecting the artistry and clarity of the product.

Method used

The design employs an optical isolation layer and a transparent protective film. By setting an optical isolation layer between the fluorescent composite material coatings and using a transparent protective film made of chitosan, silicone oil, or polyurethane during the encapsulation process, combined with laser engraving technology and the application of colored pigments, the independence of each fluorescent layer and visual clarity are achieved.

Benefits of technology

It effectively isolates optical interference from different fluorescent layers, improves the color contrast and visual effect of the finished product, extends its service life, and enhances the artistic and aesthetic value of patterns and text.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121004111A_ABST
    Figure CN121004111A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of laser engraving, and discloses a multilayer color fluorescent engraving method for bay leaves, which comprises the following steps: S1, firstly preparing a natural bay leaf material, and pretreating the prepared bay leaves for later use; s2, cutting the treated shellfish leaves into the same size, and then preparing a fluorescent composite material coating and a protective material; s3, the prepared bayberry leaves are placed on a workbench of a laser engraving machine, and engraving work is carried out; s4, after engraving is completed, a protective composite layer and a fluorescent composite material coating are smeared; and S5, finally, the carved bayberry leaf material is packaged and dried. The optical isolation layer is arranged between the fluorescent composite material coatings, so that effective isolation between different fluorescent layers is achieved, optical interference of different fluorescent response layers is avoided in the engraving process, independence and visual definition of each fluorescent layer are guaranteed, and the color contrast and the visual effect of a finished product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser engraving technology, specifically a method for engraving palm leaves using multi-layer color fluorescent technology. Background Technology

[0002] In existing multilayer coating technologies, especially in the application of fluorescent coatings, different fluorescent coatings are usually directly stacked. However, due to the different response characteristics of different fluorescent coatings to lasers, or the potential for mutual interference under external light source illumination, optical interference between coatings occurs.

[0003] During the engraving process, if there is no effective isolation between different fluorescent layers, the fluorescent effect will be blurred, affecting the clarity of the pattern and the contrast of colors, thus affecting the overall visual effect and the artistry of the product. In order to ensure the independence between fluorescent layers and avoid optical interference between them, traditional methods often have to rely on thick coatings or incompletely effective optical shielding techniques. These methods often cannot meet the requirements of high-precision, high-contrast patterns. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a method for multi-layer color fluorescent engraving using Bay leaf microstructures. This method solves the problem of mutual interference between different fluorescent coatings, which is often encountered in practical applications of traditional laser engraving. This interference prevents the optical effects between the coatings from being displayed independently, thus affecting the visual clarity and color contrast of the final product.

[0005] To achieve the above objectives, the present invention provides a method for multi-layer color fluorescent engraving of palm leaves, comprising the following steps:

[0006] S1. First, prepare natural palm leaf materials and pre-treat the prepared palm leaves for later use.

[0007] S2. Cut the treated betel leaves to the same size, and then prepare fluorescent composite material coating and protective material;

[0008] S3. Place the prepared palm leaf on the laser engraving machine table for engraving.

[0009] S4. After the engraving is completed, apply a protective composite layer and a fluorescent composite material coating.

[0010] S5. Finally, the carved palm leaf material is packaged and dried.

[0011] Preferably, in step S1, the pretreatment step includes air-drying the palm leaf material indoors for 6 to 12 hours, and cleaning and screening the surface to ensure that the palm leaves are intact and undamaged.

[0012] Preferably, in step S2, the thickness of each protective composite layer is 0.02-0.04 mm, and the coating is composed of a mixture of water-soluble silica, polyvinyl alcohol, glycerol or glycerol, transparent zinc oxide or tin oxide nanoparticles and deionized water;

[0013] The protective composite layer material has the following mass ratio: 30-60% water-soluble silica, 2-5% polyvinyl alcohol, 1-3% glycerol or glycerol, 1-3% transparent zinc oxide or tin oxide nanoparticles, and the remainder is deionized water.

[0014] Preferably, in step S2, the thickness of each layer of the fluorescent composite material coating is 0.05–0.2 mm, and the coating comprises a mixture of glue or adhesive, polyvinyl alcohol, nano-silica, fluorescent powder, and deionized water or ethanol;

[0015] The fluorescent composite material coating material has the following mass ratio: 5-15% bovine glue or adhesive, 1-5% polyvinyl alcohol, 2-10% nano-silica, 1-8% fluorescent powder, and the remainder is deionized water or ethanol.

[0016] Preferably, in step S2, an optical isolation layer is provided between the fluorescent composite material coatings, the thickness of the isolation layer is 0.05–0.3 mm, and the isolation layer material includes a carbon black film.

[0017] Preferably, in step S3, the application process of the protective composite layer and the fluorescent composite material coating includes the following steps:

[0018] S31. Apply the protective composite layer and the fluorescent composite coating according to the ratio, add them to the mixer, mix evenly, and place them in the tank for later use.

[0019] S32. Place the laser-engraved palm leaf on a table and apply coating to its surface using a scraping or spraying method. After coating, place it in a drying oven. After drying and cooling to room temperature, check whether there are bubbles or peeling on its surface.

[0020] S33. Then apply the optical isolation layer in the same manner as above, place it in a drying oven after application, and cool it to room temperature after drying.

[0021] S34. Then apply the fluorescent composite material layer according to the product requirements, using a scraper according to the shape or text.

[0022] Preferably, in step S4, the engraving work is performed using a laser system with laser focusing control and multi-wavelength output capabilities, and the graphic or text input files used for the graphic engraving are vector graphics, raster graphics, or text encoding.

[0023] Preferably, the information embedded in the fluorescent response layer includes Sanskrit, Tibetan, patterns, totems, or optically encoded identifiers, for cultural restoration or anti-counterfeiting purposes.

[0024] Preferably, in step S5, the encapsulation process uses a transparent protective film, the material of which includes chitosan, silicone oil or polyurethane, the coating thickness is 0.1–1 mm, and the drying method is natural drying or low-temperature hot air drying at 30–40℃.

[0025] Preferably, between S4 and S5, the following steps are further performed on the laser-engraved leaf before encapsulation.

[0026] Color pigments are applied using a capillary suction brush, either by hand or by inkjet printer, onto the engraved patterns and lines.

[0027] Colored pigments include colored inks, synthetic pigments, natural mineral pigments, organic pigments, and plant pigments;

[0028] After applying the powder, use a brush to apply more gold powder.

[0029] After the carving is completed, the finished product can be further sealed and stored in a vacuum bag or inert atmosphere environment for protection against moisture and heat and for long-term preservation.

[0030] This invention provides a method for multi-layer color fluorescent engraving of palm leaves. It has the following beneficial effects:

[0031] 1. This invention achieves effective isolation between different fluorescent layers by setting an optical isolation layer between the fluorescent composite material coatings. This avoids optical interference between different fluorescent response layers during the engraving process, ensures the independence and visual clarity of each fluorescent layer, and improves the color contrast and visual effect of the finished product.

[0032] 2. By using a transparent protective film during the packaging process, this invention achieves long-term protection of the coating on the shell leaf surface through a coating of chitosan, silicone oil, or polyurethane materials, preventing moisture, oxidation, and mechanical damage, while maintaining the transparency and aesthetics of the product and extending the service life of the finished product.

[0033] 3. This invention enhances the color of the engraved patterns and lines by applying colored or gold powder with a capillary suction brush after engraving. This results in richer visual layers and decorative effects on the patterns and text, making each engraved detail more artistic and aesthetically pleasing, and improving the uniqueness and beauty of the finished product. Attached Figure Description

[0034] Figure 1 This is a flowchart of a method for engraving palm leaves with multi-layer color fluorescent ink according to the present invention; Detailed Implementation

[0035] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Please see the appendix Figure 1 This invention provides a method for engraving palm leaves using multi-layer color fluorescent technology, comprising the following steps:

[0037] S1. First, prepare natural palm leaf materials and pre-treat the prepared palm leaves for later use.

[0038] S2. Cut the treated betel leaves to the same size, and then prepare fluorescent composite material coating and protective material;

[0039] S3. Place the prepared palm leaf on the laser engraving machine table for engraving.

[0040] S4. After the engraving is completed, apply a protective composite layer and a fluorescent composite material coating.

[0041] S5. Finally, the carved palm leaf material is packaged and dried.

[0042] In step S1, the pretreatment step includes air-drying the palm leaf material indoors for 6 to 12 hours, and cleaning and screening the surface to ensure that the palm leaves are intact and undamaged.

[0043] Specifically, the first step is to dry the shellfish leaves. This low-temperature drying process effectively avoids structural damage and loss of active ingredients that can be caused by high temperatures. Within this temperature range, the natural cellulose and hemicellulose in the shellfish leaves retain their original strength and flexibility, while inhibiting microbial growth caused by moisture. This improves the material's biological stability and shelf life. Unlike traditional high-temperature or natural air-drying methods, this approach ensures both drying efficiency and the integrity and functionality of the material.

[0044] The synergistic optimization mechanism of temperature-controlled drying and structural screening not only preserves the inherent advantages of natural materials but also effectively controls performance fluctuations, laying a stable foundation for various subsequent functional applications. Compared to the extensive and random nature of existing raw material processing technologies, this approach establishes a clear processing mechanism and scientific screening standards.

[0045] In step S2, the thickness of each protective composite layer is 0.02-0.04 mm, and the coating is composed of a mixture of water-soluble silica, polyvinyl alcohol, glycerol or glycerol, transparent zinc oxide or tin oxide nanoparticles and deionized water.

[0046] The protective composite layer material has the following mass ratio: 30-60% water-soluble silica, 2-5% polyvinyl alcohol, 1-3% glycerol or glycerol, 1-3% transparent zinc oxide or tin oxide nanoparticles, and the remainder is deionized water.

[0047] Specifically, the protective composite layer is designed with a multi-layer structure, which can effectively adhere to and cover the surface of the beech material. The coating is made by scientifically proportioning and mixing water-soluble silica, polyvinyl alcohol, glycerol or glycerol, transparent zinc oxide or tin oxide nanoparticles, and deionized water. Water-soluble silica, as the main skeleton material, provides structural support and interface uniformity during the film formation process, ensuring controllable thickness and complete coverage of the composite layer during coating. Polyvinyl alcohol acts as a crosslinking agent and reinforcing agent in the system, which can improve the adhesion and mechanical strength of the film. Glycerol or glycerol, as a softener, improves the flexibility and surface smoothness of the composite layer, while enhancing its compatibility with the substrate surface at the microscopic level. The addition of transparent zinc oxide or tin oxide nanoparticles endows the material with certain UV absorption capacity and antibacterial properties, achieving a balance between functionality and dispersion stability. Deionized water, as a dispersion medium, not only adjusts the overall viscosity and rheological properties, but also provides a basis for uniform distribution of the multi-component system.

[0048] The protective composite layer constructs a stable and continuous protective barrier on the surface of the beech material through interfacial film formation and synergistic mechanisms. The high specific surface area of ​​nanoparticles forms microscale functional distribution points in the coating, synergistically crosslinking with polyvinyl alcohol molecular chains to enhance the overall structural density and microscopic impermeability of the coating. Meanwhile, the glycerol component alleviates internal stress concentration caused by environmental temperature and humidity changes by regulating the degree of freedom of molecular motion within the coating, thereby effectively extending the adhesion life between the coating and the substrate. Compared with existing technologies that focus only on the single function of the coating or rely on environmentally unfriendly processes using organic solvent systems, this method, based on a water-based system and a synergistic construction approach using nanocomposite structures, achieves a green, low-temperature, and low-energy-consumption way to functionalize the surface of natural materials.

[0049] In step S2, each layer of the fluorescent composite material coating has a thickness of 0.05–0.2 mm, and the coating is composed of a mixture of glue or adhesive, polyvinyl alcohol, nano-silica, phosphor and deionized water or ethanol.

[0050] The mass ratio of the fluorescent composite coating material is 5-15% bovine glue or adhesive, 1-5% polyvinyl alcohol, 2-10% nano-silica, 1-8% fluorescent powder, and the remainder is deionized water or ethanol.

[0051] Specifically, the fluorescent composite coating is composed of glue or adhesive, polyvinyl alcohol, nano-silica, phosphor, and deionized water or ethanol. Glue or adhesive serves as the main binder, providing initial bonding strength and mechanical support, and ensuring the coating's stability under various environmental conditions, thus balancing its adhesion and transparency. Polyvinyl alcohol further enhances the coating's film-forming ability, increasing its toughness and durability. The addition of nano-silica primarily enhances the coating's structural strength and optical properties, forming a thin film with a microporous structure, ensuring its dispersibility and stability within the composite material.

[0052] The addition of phosphors endows the coating with unique luminescent properties, enabling it to emit significant fluorescence when excited at specific wavelengths. This not only enhances the visual appeal of the leaves but also increases its playability at night. Using deionized water or ethanol as solvents allows for adjustment of the coating's viscosity and flowability, as well as effective control of the drying time, ensuring uniformity and stability during film formation.

[0053] In step S2, an optical isolation layer is provided between the fluorescent composite material coatings. The thickness of the isolation layer is 0.05–0.3 mm, and the isolation layer material includes a carbon black film.

[0054] Specifically, the isolation layer material is a carbon black film. As a light-absorbing material, carbon black can effectively absorb and isolate light between different coatings, avoiding unnecessary light scattering or reflection from affecting the fluorescence effect. Within its specific microstructure, the carbon black film can uniformly disperse light, allowing different fluorescent layers to emit light effectively within their respective spectral ranges without optical overlap or signal attenuation due to mutual interference.

[0055] Carbon black film has excellent optical isolation properties, which can enhance the durability of the coating. In application scenarios where the coating is exposed to light for a long time, it can ensure the stability of the fluorescent layer and its luminescence performance. It can provide sufficient optical isolation effect without significantly increasing the weight of the coating or affecting the flexibility of the entire coating system.

[0056] Step S3, the application process of the protective composite layer and the fluorescent composite material coating, includes the following steps:

[0057] S31. Apply the protective composite layer and the fluorescent composite coating according to the ratio, add them to the mixer, mix evenly, and place them in the tank for later use.

[0058] S32. Place the laser-engraved palm leaf on a table and apply coating to its surface using a scraping or spraying method. After coating, place it in a drying oven. After drying and cooling to room temperature, check whether there are bubbles or peeling on its surface.

[0059] S33. Then apply the optical isolation layer in the same manner as above, place it in a drying oven after application, and cool it to room temperature after drying.

[0060] S34. Then apply the fluorescent composite material layer according to the product requirements, using a scraper according to the shape or text.

[0061] Specifically, first, the components of the protective composite layer and the fluorescent composite coating are added to a mixer in a predetermined ratio and mixed. This ensures that each component is evenly distributed during mixing to form a homogeneous coating. The mixed coating should be stored in a dedicated container for later use to prevent prolonged exposure to air, which could lead to component stratification or volatilization.

[0062] Next, place the cut beech leaf material on a flat table, ready for coating. Apply the mixed protective composite layer and fluorescent composite material coating to the surface of the beech leaf using either a scraping or spraying method. Scraping is suitable for large areas requiring uniform coating, while spraying is better suited for detailed coating operations. After coating, place the beech leaf in a drying oven to ensure the coating dries quickly under temperature control. Once dry, allow the coating to cool to room temperature and check for bubbles or peeling to ensure the integrity and uniformity of the coating. Apply the optical isolation layer using the same method. After application, allow the beech leaf material to air dry again indoors to ensure the stability and uniformity of the optical isolation layer. This process ensures the optical isolation effect between the protective composite layer and the fluorescent composite layer, avoiding optical interference between layers. Depending on product requirements, use a scraper or other appropriate tools to apply the fluorescent composite material layer. If specific shapes or text effects are required, they can be achieved by precisely controlling the position of the scraper or spraying tool.

[0063] In step S4, the engraving work uses a laser system with laser focusing control and multi-wavelength output capabilities to engrave graphics and text. The graphic or text input files used for graphic engraving are vector graphics, raster graphics, or text codes.

[0064] Specifically, the focusing and control of the laser system allows the energy of the laser beam to be concentrated in a very small area. During the graphic engraving process, by selecting different laser wavelengths, a specific layer in the coating is selectively excited. Different fluorescent layers have different absorption characteristics for specific wavelengths of light. Therefore, adjusting the laser wavelength allows different layers of fluorescent materials to be excited in the desired area, thereby achieving the fluorescent display of patterns or text.

[0065] Laser engraving can use vector graphics, raster graphics, or text encoding as input files, which accurately convey the desired engraving patterns, text, and details. During the engraving process, the laser system precisely engraves according to the pattern or text data provided in the input file, following a set path and depth. Because the laser wavelength and engraving depth can be precisely controlled, the fluorescence effect of each part of the pattern or text on the surface depends on the matching of the wavelength and engraving depth, thereby achieving the control of the layering and color distribution between layers. This significantly improves the durability of patterns and text while maintaining high precision and low energy consumption. Furthermore, because the temperature of the heated areas on the material surface can be precisely controlled during laser engraving, the engraving effect is more stable, avoiding material damage or coating degradation caused by overheating.

[0066] The information embedded in the fluorescent response layer includes Sanskrit, Tibetan, patterns, totems, or optically encoded identifiers, used for cultural restoration or anti-counterfeiting purposes.

[0067] Specifically, firstly, the embedding of traditional cultural characters such as Sanskrit and Tibetan not only has the significance of cultural restoration but also plays a crucial role in anti-counterfeiting systems. By embedding these cultural characters into fluorescent responsive layers, texts or patterns that are difficult to detect under normal lighting can become visible under specific lighting conditions, thus increasing the difficulty of anti-counterfeiting applications. Because these texts and patterns are closely related to the layers of fluorescent materials, laser engraving technology, through precise wavelength control, can selectively excite these fluorescent layers, causing them to produce different visual effects between layers. This not only protects cultural heritage but also improves the accuracy and security of identification.

[0068] Secondly, the embedding of cultural symbols such as patterns and totems focuses more on visual effects. By embedding meaningful patterns or totems into the fluorescent responsive layer, these symbols can exhibit different optical properties under different wavelengths of light. The precision of laser engraving ensures that the patterns and totems present high-resolution images on the material surface, not only providing excellent visual effects but also enabling them to play an unreplicable role in anti-counterfeiting systems. The embedding and display of information in the fluorescent responsive layer relies on a precise laser engraving and wavelength matching mechanism. Each layer of fluorescent material has unique response characteristics to different wavelengths of laser light. By adjusting the wavelength and engraving depth, laser engraving can precisely control the display position and effect of patterns, text, or coded information.

[0069] In step S5, the encapsulation process uses a transparent protective film, the material of which includes chitosan, silicone oil or polyurethane, the coating thickness is 0.1–1 mm, and the drying method is natural drying or low-temperature hot air drying at 30–40℃.

[0070] Specifically, chitosan, as a natural polymer material, has good biocompatibility and transparency, providing some protection for the coating and possessing mild antibacterial properties; silicone oil has waterproof, moisture-proof, and antioxidant capabilities, which can improve the weather resistance and stability of the encapsulation film; polyurethane has excellent mechanical strength and anti-friction properties, effectively enhancing the coating's scratch resistance and abrasion resistance. By precisely proportioning these three materials, comprehensive physical protection can be provided while ensuring transparency, preventing damage to the coating from external environments, including moisture, pollution, and mechanical damage.

[0071] Encapsulation is not merely a simple physical covering; it involves selecting appropriate materials and processes to maximize product lifespan and stability. By employing materials such as chitosan, silicone oil, or polyurethane, encapsulation films can maintain high transparency while providing protective properties, preventing damage to the surface coating from ultraviolet rays, moisture, and dust.

[0072] Between S4 and S5, the following steps are also performed on the laser-engraved Baye leaf before packaging.

[0073] Color pigments are applied using a capillary suction brush, either by hand or by inkjet printer, onto the engraved patterns and lines.

[0074] Colored pigments include colored inks, synthetic pigments, natural mineral pigments, organic pigments, and plant pigments;

[0075] After applying the powder, use a brush to apply more gold powder.

[0076] After the carving is completed, the finished product can be further sealed and stored in a vacuum bag or inert atmosphere environment for protection against moisture and heat and for long-term preservation.

[0077] Specifically, after laser engraving, the engraved patterns and lines on the palm leaf material are applied using a capillary suction brush. The brush picks up colored or gold powder, which is then directly applied to the engraved patterns and lines. This process not only adds visual depth and color to the patterns and lines but also makes the engraved designs more striking and artistic. The application of colored or gold powder enhances the overall aesthetic appeal of the palm leaf material after engraving.

[0078] Pigments are mainly classified into the following categories:

[0079] Natural mineral pigments include:

[0080] Gold and silver: used to outline lines or embellish the image, giving Thangka a luxurious texture;

[0081] Cinnabar: Primarily used for its red color; it is bright in color but contains toxins.

[0082] Lapis lazuli: provides a blue color that is pure and long-lasting;

[0083] Turquoise and malachite: used for green and blue-green respectively, with stable colors;

[0084] Realgar and orpiment: used for the color of yellow, they have a certain degree of toxicity;

[0085] Red lead and black ink: used for black and red colors, with pure colors.

[0086] Plant-based pigments include:

[0087] Saffron and madder: Extract red and orange hues, resulting in vibrant colors;

[0088] Indigo: used for the color blue, giving it a fresh and clean look;

[0089] Golden lotus: Extract the yellow color, resulting in a bright color;

[0090] Organic matter includes:

[0091] Pearls and coral: ground into powder and used in white and red to add depth to the image;

[0092] Bone-based pigments: such as clam shells, dragon bones, etc., used for special effects.

[0093] Synthetic pigments include acrylic pigments, which are less expensive but may not have the same artistic value as natural pigments.

[0094] The pigments are mainly natural mineral and plant pigments. These pigments are not only brightly colored, but also have the characteristics of being long-lasting and fading-free, reflecting the respect for and use of natural materials in traditional craftsmanship.

[0095] Based on the above steps and materials, when it is necessary to further improve the fluorescence effect, when preparing the color material, the phosphor is added to the pigment again for mixing, and then the pigment is used to further draw or spray the pattern and line through an inkjet printer or capillary suction brush.

[0096] After being coated with color or gold powder, the engraved finished products will undergo further packaging to ensure they are not affected by external environmental factors such as moisture and oxygen during storage. The finished products can be placed in vacuum bags or sealed in an inert atmosphere for storage. Vacuum bag packaging effectively removes moisture and oxygen from the air, preventing moisture from corroding and affecting the shell material and coating; while inert atmosphere packaging, by filling with inert gases such as nitrogen, prevents oxidation reactions and further improves stability during long-term storage.

[0097] Example 1:

[0098] Material preparation: Use natural palm leaves, clean the surface and dry at 40℃ to 50℃ for 12 hours;

[0099] A fluorescent composite coating was prepared using water-soluble silica, polyvinyl alcohol, glycerol, transparent zinc oxide nanoparticles, and deionized water. The ratio of water-soluble silica was 60%, polyvinyl alcohol was 5%, glycerol was 3%, zinc oxide nanoparticles were 2%, and the remainder was deionized water. The thickness of the protective composite layer was 0.02 mm.

[0100] A fluorescent composite coating was prepared using cow glue, polyvinyl alcohol, nano silica, phosphor, and ethanol, with the following proportions: 10% cow glue, 3% polyvinyl alcohol, 5% nano silica, 4% phosphor, and the remainder ethanol.

[0101] All coatings are applied using a scraping method and dried to room temperature. During laser engraving, multi-wavelength lasers are used to engrave the graphics, and the output graphics are vector graphics. After engraving, the shell material is encapsulated with a transparent protective film made of chitosan. The coating thickness is 0.05 mm, and low-temperature hot air drying is used.

[0102] Example 2:

[0103] Differences from Example 1: The water-soluble silica in the fluorescent composite material was reduced by 10%, the drying temperature was reduced from 60% to 50%, the coating thickness of the encapsulation material was reduced from 0.05 mm to 0.1 mm, and all other parameters remained the same, with a protective composite layer of 0.03 mm.

[0104] Example 3:

[0105] Differences from Example 2:

[0106] The amount of water-soluble silica in the fluorescent composite material was reduced by 10%, the drying temperature was reduced from 50% to 40%, the coating thickness of the encapsulation material was increased to 0.2 mm, which is 1 mm more than in Example 2, and all other aspects were the same. The adhesive used was glue, and the protective composite layer was 0.04 mm thick.

[0107] Comparative Example 1:

[0108] Compared to Example 1, the difference is that water-soluble silica was removed, and glue was used as the adhesive; otherwise, they are the same.

[0109] Comparative Example 2:

[0110] Compared to Example 2, the difference is that the water-soluble silica is increased by 10% (to 60%), while the rest are the same.

[0111] Comparative Example 3:

[0112] Compared with Example 3, the difference is that the coating thickness of the encapsulation material is 0.1 mm, and all other aspects are the same.

[0113] Table 1: Material Validation Table for Examples and Comparative Examples

[0114]

[0115]

[0116]

[0117] Table 1 shows that in Example 1 and Comparative Example 2, a reduction in water-soluble silica can affect the stability, strength, or surface properties of the composite material, potentially leading to decreased coating adhesion and durability. Example 1 used a drying temperature range of 40°C to 50°C, Example 2 lowered the drying temperature to 50°C, and Example 3 further lowered it to 40°C. This demonstrates that excessively high or low drying temperatures can affect the uniformity of coating drying and the adhesion of the material. Lower drying temperatures may result in insufficient drying of the coating, thus affecting its performance.

[0118] The coating thickness of the encapsulation material in Example 1 was 0.05 mm. The coating thicknesses in Example 2 and Comparative Example 3 were reduced to 0.1 mm and increased to 0.2 mm, respectively, demonstrating that changes in encapsulation thickness directly affect the protective performance of the material. A coating that is too thin may result in insufficient protection and susceptibility to external factors; while a coating that is too thick may affect the optical or mechanical properties of the material, leading to other negative effects.

[0119] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for engraving palm leaves using multi-layer color fluorescent technology, characterized in that, Includes the following steps: S1. First, prepare natural palm leaf materials and pre-treat the prepared palm leaves for later use. S2. Cut the treated betel leaves to the same size, and then prepare fluorescent composite material coating and protective material; S3. Place the prepared palm leaf on the laser engraving machine table for engraving. S4. After the engraving is completed, apply a protective composite layer and a fluorescent composite material coating. S5. Finally, the carved palm leaf material is packaged and dried.

2. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S1, the pretreatment step includes air-drying the palm leaf material indoors for 6 to 12 hours, and cleaning and screening the surface to ensure that the palm leaves are intact and undamaged.

3. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S2, the thickness of each protective composite layer is 0.02-0.04 mm, and the coating is composed of a mixture of water-soluble silica, polyvinyl alcohol, glycerol or glycerol, transparent zinc oxide or tin oxide nanoparticles and deionized water. The protective composite layer material has the following mass ratio: 30-60% water-soluble silica, 2-5% polyvinyl alcohol, 1-3% glycerol or glycerol, 1-3% transparent zinc oxide or tin oxide nanoparticles, and the remainder is deionized water.

4. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S2, the thickness of each layer of the fluorescent composite material coating is 0.05–0.2 mm, and the coating is composed of a mixture of glue or adhesive, polyvinyl alcohol, nano-silica, fluorescent powder, and deionized water or ethanol. The fluorescent composite material coating material has the following mass ratio: 5-15% bovine glue or adhesive, 1-5% polyvinyl alcohol, 2-10% nano-silica, 1-8% fluorescent powder, and the remainder is deionized water or ethanol.

5. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S2, an optical isolation layer is provided between the fluorescent composite material coatings. The thickness of the isolation layer is 0.05–0.3 mm, and the isolation layer material includes a carbon black film.

6. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S3, the application process of the protective composite layer and the fluorescent composite material coating includes the following steps: S31. Apply the protective composite layer and the fluorescent composite coating according to the ratio, add them to the mixer, mix evenly, and place them in the tank for later use. S32. Place the laser-engraved palm leaf on a table and apply coating to its surface using a scraping or spraying method. After coating, place it in a drying oven. After drying and cooling to room temperature, check whether there are bubbles or peeling on its surface. S33. Then apply the optical isolation layer in the same manner as above, place it in a drying oven after application, and cool it to room temperature after drying. S34. Then apply the fluorescent composite material layer according to the product requirements, using a scraper according to the shape or text.

7. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: In step S4, the engraving work is carried out using a laser system with laser focusing control and multi-wavelength output capability for graphic engraving. The graphic or text input files used for graphic engraving are vector graphics, raster graphics, or text encoding.

8. The method for multi-layer color fluorescent engraving of palm leaves according to claim 7, characterized in that: The information embedded in the fluorescent response layer includes Sanskrit, Tibetan, patterns, totems, or optically encoded identifiers, used for cultural restoration or anti-counterfeiting purposes.

9. The method for engraving palm leaves using multi-layer color fluorescent inks according to claim 1, characterized in that: In step S5, the encapsulation process uses a transparent protective film, the material of which includes chitosan, silicone oil or polyurethane, the coating thickness is 0.1–1 mm, and the drying method is natural drying or low-temperature hot air drying at 30–40℃.

10. The method for multi-layer color fluorescent engraving of palm leaves according to claim 1, characterized in that: Between S4 and S5, the following steps are also included: performing the laser-engraved bayonet leaf before packaging. Color pigments are applied using a capillary suction brush, either by hand or by inkjet printer, onto the engraved patterns and lines. Colored pigments include colored inks, synthetic pigments, natural mineral pigments, organic pigments, and plant pigments; After applying the powder, use a brush to apply more gold powder. After the carving is completed, the finished product can be further sealed and stored in a vacuum bag or inert atmosphere environment for protection against moisture and heat and for long-term preservation.